PENGARUH PENGETAHUAN DAN SIKAP TERHADAP NIAT BELI PRODUK RAMAH LINGKUNGAN (STUDI KASUS PADA PERTAMAX DI KOTA DENPASAR) - Suwarso, Nurul Hidayah Eko; Wulandari K, Ni Made (E-Jurnal Manajemen, 2015)
This study aims to find out the influence of environmental knowledge on the intention to buy environmentally friendly products. It is also to find out the influence of consumer attitudes on the environment on the intention to buy environmentally friendly products, as well as figuring out the role of attitudes on the environment in mediating the effect of environmental knowledge on the intention to buy environmentally friendly products Pertamax. The study was conducted in Denpasar, on consumers who have a motor vehicle and still use fuel (fuel oil) Premium. The sampling method used in this study is a non-probability sampling technique in particular incidental and purposive sampling. Data collected through questionnaires. The samples used in this study was 100 respondents. The data collected were processed using analytical techniques PLS (Partial Least Square) and Test Sobel. Test results showed that all variables in this study are valid and reliable and the results of this study indicate that knowledge of the environment has a positive and significant impact on the intention to buy environmentally friendly products and consumer attitudes on the environment. Variable consumer attitudes on the environment has a positive and significant influence and mediate the effects of environmental knowledge on the intention to buy environmentally friendly products
Keywords: pengetahuan lingkungan; sikap konsumen; niat beli